Sphaerocetum gen. n., a new genus of the Protosternini from Peninsular Malaysia (Coleoptera: Hydrophilidae: Sphaeridiinae) - Fikáček, Martin (Zootaxa, 2010)
A new genus and species of the tribe Protosternini, Sphaerocetum malayanum gen. & sp. n., is described from the peninsular Malaysia (Perak). A detailed description is provided along with habitus photographs, line drawings and SEM micrographs of relevant diagnostic characters. Although clearly belonging to the Protosternini, the new genus varies in several characters previously considered as uniform within the tribe; these characters are discussed in detail. An updated identification key to protosternine genera is also provided.